PENGARUH PENEREPAN METODE KARYAWISATA TERHADAP PEMBELAJARAN SOSIOLOGI - Yanto Nong Bola (Sociology Education, Teaching Training and Education Faculty, Muhammadiyah University of Kupang, 2020)
This study aims to determine the application of the field trip method in sociology learning in SMA Negeri 8 Kupang. This research is a quantitative method that is intended to find out whether there is an influence of the study tour method in schools using the formula p = f / nx100%. The subjects of this study were students of class XI IPS 3 even semester 2019-2020 with a total of 29 students. Data collection techniques in this study using questionnaires and test results. The results of this study indicate that the implementation of learning using the field trip method in sociology subjects can influence student learning outcomes with a percentage of 87.24%. This result can also be known from the student learning outcomes with an average of 79.3 or with a percentage of completeness of 86.20%. This result has reached the KKM standard determined by the SMA Negeri 8 Kupang which is 70.